Promoting indigenous knowledge of Stixis suaveolens (Roxb.) Baill.: A neglected underutilized wild edible and medicinal plant for enhancing food and health security among the Ao tribe of Mokokchung district, Nagaland, India - Gyati Yam; Joynath Pegu (Ethnobotany Research and Applications, 2026)
Background: Neglected and underutilized species (NUS) are valuable plant resources that have immense potential for improving food and health security. Stixis suaveolens (Roxb.) Baill. is an endemic plant species belonging to the family Resedaceae and a climbing shrub that has great ethnobotanical significance among the Ao tribe of Nagaland. However, its ethnobotanical importance has not been quantitatively evaluated. Methods: This study investigates the traditional knowledge system and its use pattern through Relative Frequency of Citation (RFC) and Plant Parts Value (PPV). Results: The species showed a high RFC value (0.77), demonstrating the importance and recognition of the species among the informants. PPV analysis showed that fruits have the highest usage value (0.46) compared to other parts like flowers (0.23), roots (0.15), and leaves (0.15). The results demonstrate a clear utilization pattern, with fruits serving as the primary edible component, while other plant parts are mainly associated with therapeutic uses. Conclusions: The findings highlight S. suaveolens as promising NUS, emphasizing the need for its conservation, sustainable use, promotion, and further scientific validation. Keywords: Ao tribe, Stixis suaveolens, neglected and underutilized species, Nagaland.